PEMANFAATAN MATERIAL ALAM LOKAL DESA LAMDESAR TIMUR PULAU LARAT KABUPATEN MALUKU TENGGARA BARAT SEBAGAI BAHAN LAPIS PONDASI JALAN YANG DISTABILISASI DENGAN SEMEN - Rosida Lestaluhu; Soumokil H. Johny; David Daniel M. Huwae (Journal Agregate, 2023)
Road infrastructure development in outermost and remote or limited areas is one of the current government's priority programs in realizing its vision and mission. However, along the way, there is limited availability of quality road materials according to specifications. So that the construction of road infrastructure requires high costs. Actually, there are quite a lot of local materials, such as granular materials in the form of a mixture of sand and stone (sirtu) and limestone or coral materials, but they cannot be used optimally for road pavement because they do not meet the specifications or requirements. often known as substandard local materials. Utilization of local materials such as in East Lamdesar Village can be used as an alternative to overcome the problem of road construction in that location. The problem is that the quality of the material at that location is not known whether it is in accordance with specifications (standard material) or below standard (substandard). For this reason, it is necessary to carry out a series of research in the laboratory, so that the properties of the material are known. By knowing the properties of the material so that it can be ascertained whether or not it can be used as a cement foundation layer for road pavement.  The research was conducted using experimental methods through laboratory testing. The results showed that local material stabilization with cement resulted in a high compressive strength value. The value of the compressive strength is higher according to the increasing percentage of cement content used. The results of the filter analysis test that entered the foundation layer gradation were 100% and the compressive strength value that met the requirements of special specifications with a cement content of 6% was 36.19 kg/cm2. Referring to the value of the resulting compressive strength (generally 25-40 kg/cm2) then the local material of East Lamdesar Village can be used as a class A foundation layer for road pavement, and for its use or application in the field, specifications are needed as recommended based on research results. this.